(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
Particle size distribution (PSD) affects soil behaviour and plays a main role in geotechnical engineering. In site investiga- tions of large engineering structures, in earthquakes and liquefaction research and before filter material selection, it is necessary to make a number of PSD analyses. There are two popular techniques to determine PSD in the lab: sieving for the coarse-grained samples and hydrometer analysis for fine-grained samples. However, determining the PSD of soil in the lab has some challenges such as time, labour, difficulty and errors related to the analysis. The newly developed dy- namic image analysis (DIA) method based on wavelet transformation (WT) analysis is used as the main approach for determining particle size distribution. The DIA method contains saving the image and processing it with the software for a specified goal. The DIA method holds many advantages over the hydrometer analysis, including automating the test, reducing errors, monitoring and evaluating the particles at any time. In this paper, the PSD of fine-grained soil with a plasticity index (PI(=30 has been determined. The images of soil were prepared with a digital camera at a different time when particles settled through a sedimentation cylinder and were analysed with MATLAB software. The results were compared with the hydrometer analysis. The results showed that at t=15 min, a complete overlapping was seen between the DIA method and hydrometer analysis. The D20, D50 and D80 values by the DIA method were determined respectively, 0.0017, 0.012 and 0.031 mm at t=15 min. The results demonstrated that the DIA technique can be implemented for all types of fine-grained soils, more easily than the hydrometer analysis. The differences between the methods’ results were raised due to the amount of data provided by them.